A Study on the Feasibility and Utility of Continuous Glucose Monitors in Elite Football - Sophie Harries; David J. Clayton; Michael A. Johnson; Ross Burbeary; Robin T. Thorpe; Ian Varley (Journal of Sports and Exercise Medicine, 2025)
Physiological performance may be limited by reduced systemic glucose availability to working muscles. Continuous glucose monitors (CGM) measure interstitial glucose every 1-15 minutes, offering a practical way to assess glucose during sporting activity. However, empirical research has predominantly focused on endurance-based sports, whereas glucose responses during professional competitive football matches remain unknown. This study evaluated the feasibility and utility of CGM in professional football. Eight professional, male outfield footballers from the English third tier participated in the study. Participants completed a 14-day food diary control period, followed by a 28-day observation period wearing CGM devices during six matches and sixteen training sessions. CGM devices remained in situ for 98% of training sessions and matches. Mean glucose concentrations were 6.5 ± 1.2 mmol/L during training sessions, 7.5 ± 2.1 mmol/L during match play, and 5.4 ± 0.3 mmol/L overnight. No significant differences were found between glucose concentrations during match play (p = 0.060) or training (p = 0.510), compared to overnight fasted glucose concentrations. There was also no difference between training and match-play glucose concentrations (p = 0.788). Glucose concentrations were highly individualised, with one player displaying minimal change throughout match play (-0.2 mmol/L) whereas another experienced increases of up to 5.8 mmol/L. Non-nutritional factors appeared to influence glucose concentrations; participants (n=3) who used nicotine pouches displayed an transient increase in blood glucose in the 10-55 minutes after administration. This study concludes that CGM use in professional football is feasible for assessing individual glucose responses to training and match-play.
Keywords: Glucose